Research design of decision support system for team sport - Zainol Abidin, Mohammad Zukuwwan; Mohd Nawawi, Mohd Kamal; Mat Kasim, Maznah (2016)
This paper proposes a suitable research procedure that can be referred to while conducting a Decision Support System (DSS) study, especially when the development activity of system artifacts becomes one of the research objectives.The design of the research procedure was based on the completion of a football DSS development that can help in determining the position of a player and the best team formation to be used during a game.After studying the relevant literature, we found that it is necessary to combine the conventional rainfall System Development Life Cycle (SDLC) approach with Case Study approach to help in structuring the research task and phases, which can contribute to the fulfillment of the research aim and objectives.